Creative-Motivated Citizen Science After-School STEAM Programme for Motivating Actions Related to the Oceanic Microplastics Problem - Tomomi Sayuda; Haruyuki Kinoshita; Fumitoshi Kato; Miles Pennington (Citizen Science: Theory and Practice)
Citizen science (CS) projects focused on microplastics (MP), small plastics that cause widespread ocean pollution, have gained interest from international research communities. However, research is lacking on designing citizen science educational programmes that promote microplastic problem-solving and enhance local understanding. These programmes could use STEAM (Science, Technology, Engineering, Art, and Math) education and creative activities for children, supported by local adults such as parents and teachers. We, therefore, created a nine-week STEAM education CS after-school programme for primary school children. In addition to MP sampling, we have also incorporated elements of STEAM education, combining creative projects and motivational activities, in this creative-motivated after-school programme. Our goals are to encourage long-term community cooperation in research, learning about MP issues, and thinking about local solutions through this community participatory CS programme. As a result, our qualitative results showed that five primary school children and five community adults were actively involved in the programme. Three creative project outputs were produced, and four MP data sampling sessions were conducted. Three pairs of children and their mother participants remained engaged in this ongoing problem-solving activity 10 months after its conclusion. During our programme progression, we observed familial engagement between local children and parents, which has not commonly been studied in the context of CS programmes. We believe that designing action-motivating long-term programmes to raise participants’ awareness of issues and interest in research is important. This CS programme has the potential to encourage long-term community interaction with research and enhance community involvement in environmental issues.